«No·m direu que lo dit Sèneca sia propheta ne patriarcha, qui parlen figurativament»: Antoni Canals i el «De Providentia» - Martínez, Tomàs (Caplletra. Revista Internacional de Filologia, 2015)
The author argues that in his version of Séneca’s De providentia, as indeed in other of his versions, Canals does not show any evidence of having assimilated the ideological tenets of the Humanism and the Renaissance. On the contrary: for him classical sources are merely used as means to underline an orthodox and religious discourse.